THE LITTER PRODUCTIVITY OF MERANTI (Shorea spp.) TREES IN ARBORETUM AREA OF RIAU UNIVERSITY PEKANBARU - Arya Irawan; Rudianda Sulaeman; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The litter productivity is the estimated quantity of biomass leaf, twig and plant of reproduction material (flower) which fall down from tree species in different type of ecosystem community. Arboretum was covered with many types of trees among them was the meranti (Shorea spp.) tree as a producer of litter but not yet known how much productivity resulting litter. This research was conducted in the arboretum area of Riau University on December 2014 – January 2015. The purpose of this research was to determine the amount of litter productivity meranti (Shorea spp.) tree in the arboretum area of Riau University Pekanbaru. The research result showed that the litter productivity is affected by rainfall and wind velocity.The greatest litter productivity of meranti (Shorea spp.) tree occurred in the second week with rainfall 27,6 mm/day and wind velocity NE/08 m/s. The most litter productivity is on leaves organ (68 %) for the leaves have a short life cycle, twigs organ (24 %), fruits (5 %) and flowers (3 %). D tree is the tree that has the highest litter productivity for having large diameters and height tree, while the production of flower and fruit found in the largest C tree because these tree was in a productive period. Keywords: productivity, litter, meranti, arboretum